The two-hour marathon: What's the equivalent for women? - Hunter, S. K.; Joyner, M. J.; Jones, A. M. (Journal of Applied Physiology, 2015)
The principal characteristic of the runner who may break the two-hour barrier in the marathon will be their sex: the person will be male. The fastest men outperform the fastest women because of sex differences in physiology including a higher VO2 max. This viewpoint addresses the questions of what is the two-hour equivalent for women, and who will break this barrier? The current sex difference in the world record for the marathon is ~10% which is slightly less than the mean sex difference in performance usually documented between elite men and women distance runners. Based on comparisons of the top 50 marathon times run by men and women, we argue that Paula Radcliffe's world record of 2:15:25 (hr:min:s) set in 2003 is at least equivalent to a two-hour marathon for women. We also provide evidence that there is less depth in elite women's distance running, in part, due to historical and social factors that have led to less opportunity for women than men.